Development of Power Management System for Electric Power Generation in Tanker Ship Based on Simulation - Indra Ranu Kusuma; Raynaldi Pratama (International Journal of Marine Engineering Innovation and Research, 2017)
Power management system (PMS) for electric power generation in ship, in the case of tanker ship, is the system that has function to control and to monitor all generators in ship as the main electricity supplier for all electric equipments or installed load. The number of total load that supplied by generator depends on the frequency of the use of load itself which would be read in PMS as well. It leads the operator to take a decision on how many generator should be operate whether in parralel or stand alone operation to fulfilling the power needs. Those loads should be grouped into essential and non essential load. This groups affecting the performance of the generators, where it will covers the maximum load at 306.67 kw under the condition of all electric equipments are operated well while the cargo handling of tanker ship is on process. However, in the state of emergency while the non essential electrical equipments are being cut off trough PMS, the generator will only covers the the maximum load at 253.88 kw to fulfilling the same needs. In the extreme case (total efficiency of parralel operation at 70%), the generators would cover the total load at 306.6 kw still by sparing the generated power of 52.72 kw.